2019
DOI: 10.1024/0301-1526/a000834
|View full text |Cite
|
Sign up to set email alerts
|

ESVM Guideline on peripheral arterial disease

Abstract: Tel. +41 (0) 31 300 45 00, verlag@hogrefe.ch, www.hogrefe.ch Media ManagerJosef Nietlispach, Tel. +41 (0) 31 300 45 69, inserate@hogrefe.ch SubscriptionsTel. +41 (0) 31 300 45 55, zeitschriften@hogrefe.ch ProductionReto Mastria, Tel. +41 (0) 31 300 45 73, reto.mastria@hogrefe.ch Frequency 6 issues per volumeVasa is the official organ of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
193
0
31

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(224 citation statements)
references
References 419 publications
(420 reference statements)
0
193
0
31
Order By: Relevance
“…The microcirculatory diagnostic has already proved to have a good prognostic value in clinical practice in not ICU patients. The nailfold capillaroscopy or transcutaneous oxygen pressure measurement (TcpO2) are routinely used, the first in the diagnostic pathway of the Raynaud's phenomenon, the latter in the selecting critical limb ischemia and predicting healing of skin lesions [61,62].…”
Section: Is the Beside Microcirculation Assessment A Compelling Needmentioning
confidence: 99%
“…The microcirculatory diagnostic has already proved to have a good prognostic value in clinical practice in not ICU patients. The nailfold capillaroscopy or transcutaneous oxygen pressure measurement (TcpO2) are routinely used, the first in the diagnostic pathway of the Raynaud's phenomenon, the latter in the selecting critical limb ischemia and predicting healing of skin lesions [61,62].…”
Section: Is the Beside Microcirculation Assessment A Compelling Needmentioning
confidence: 99%
“…Peripheral arterial disease is a severe medical condition associated with high morbidity, mortality, and significant socioeconomic and social impacts. Increased incidence of renal failure, cardiovascular disease, diabetes mellitus with associated microangiopathy and retinopathy are documented in patients with PAD [1,2].…”
Section: Critical Limb Ischemiamentioning
confidence: 99%
“…Most recently, the 2019 guidelines published by the European Society for Vascular Medicine (ESVM) take up the ongoing discussion on the meta-analysis by Katsanos et al [18]. Based on a secondary analysis of patient-level data from the LEVANT trial [29] and one of several available observational studies with routinely collected data, the authors concluded that the treatment of femoropopliteal lesions with coated balloons can be recommended as a standard of care (recommendation class II) [14].…”
Section: Introductionmentioning
confidence: 99%